(untitled) (Revista Apotheke, 2022)
For the master’s research at PPGARTES-UFC, I used the time frame from 2018 to 2020 to delimit my collection of archived documents to be reviewed and post-produced for artistic creation. I justify the choice of clipping and describe situations, self-analysis and memories of that specific period. Using techniques such as pattern identification, filtering and grouping to rearrange data from my daily life, I propose the autofictional persona Amari, for which, in this text, I present the narrative trajectory: a journey between cities and modes of transport. To deal with the encounter and the relationships between elements (tangible and intangible), I use the network image (in different technological approaches) and adopt the thoughts of Ingold (2015) on pilgrimage and ways of knowing. Through five reports of personal experiences, I simulate crisis scenarios, expose the process and seek to communicate the context (the vision) in which this research arises and develops. Finally, this article reflects on nomadism in territories, in fields of knowledge and in human interaction with the digital.